Evaluation of the determinants of food security within the COVID-19 pandemic circumstances- a particular case of Shaanxi, China - Apurbo Sarkar; Wang Hongyu; Abdul Azim Jony; Jiban Chandro Das; Waqar Hussain Memon; Lu Qian (BMC, 2021)
Abstract Background Agricultural food production and distribution industries may play a vital role in determining the current conditions of any country's food security and sustainable development goals. This paper examined the determinants of food security within three distinct aspects (effective utilization of food, food availability, and food access) within the COVID-19 epidemic situation. Methods The qualitative set-up of the study comprised with the identification of drivers by critical analysis of published papers and discussion held with some practitioners. The quantitative data used in this research were collected from a survey covering the agricultural food supply industry in China (Shaanxi Province). The survey was conducted from November to December 2020 and we mainly focus on three aspects of food security (effective utilization of food, food availability, and food access). The core analytical assumptions were made by employing exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM). Results After analyzing the data collected from 257 agricultural food productions and distribution personnel along with the hypothesis testing, it found that the determinants of the effective utilization of food were positively related to the determinants of food access (β = 0.291, p = 0.029) and food availability (β = 0.298, p = 0.011), and the determinants of food availability were positively related to the food access determinants (β = 0.128, p = 0.002). The association and variance values between food availability and food access were 0.659 and 0.407; the association and variance values between for effective utilization of food and food availability aspects were 0.465 and 0.298, and between effective utilization of food and economy were 0.508 and 0.475. Conclusion The study critically evaluated the interconnection among the crucial determinants within the banner of three dimensions, which will act as a major contribution to existing literature. This research will help the government and industry to develop policies and strategies for the successful implementation of all the associated determinants of food security in terms of the epidemic situation.